Analisis Efisiensi dan Efektivitas Pengelolaan Anggaran Belanja Pegawai Pada Dinas Perindagkop dan UKM Kabupaten Pulau Morotai - Jamiludin Hasan; Ardin Umar; Nurafni Kurung (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the level of efficiency and effectiveness. The results of the efficiency ratio analysis show that the average level of efficiency of budget management at the Office of Industry and Trade and UKM of Morotai Island Regency during 2017 was 1.01%, in 2018 it was 1.12% and in 2019 it was 1.19. This means that budget management is carried out very efficiently. The management of the employee expenditure budget at the Office of Industry and Trade and UKM of Morotai Island Regency has met the requirements of efficiency, namely the use of minimum funds to achieve maximum results, while the results of the effectiveness ratio analysis show the average ratio of the effectiveness of budget management of the Office of Cooperatives and Small and Medium Enterprises of Morotai Island Regency in 2017 95.55%, in 2018 88.68% and in 2019 84.03%. This means that budget management has met the criteria for being very effective because budget realization has approached the predetermined budget target.